Ventricular rhythm disturbances during computer spirography in patients with stable ischemic heart disease and chronic obstructive pulmonary disease: clinical and functional predictors of occurrence - Yu. M. Mostovoi; L. V. Rasputina; D. V. Didenko; A. O. Dovhan (Zaporožskij Medicinskij Žurnal)
The purpose of the study is to determine the predictors of cardiac rhythm disturbance during spirography in patients with a combination of stable coronary heart disease and chronic obstructive pulmonary disease.